The Implementation of Legal Protection against Children Who Commit Criminal Acts in the Judicial Process in Indonesia - Wahyuningsih, S.E. (International Journal of Psychosocial Rehabilitation, 2020)
In Indonesia, a child in conflict with the law is attempted to be resolved through a version before the court stipulated in the Law No. 11/2012 of the Child criminal justice system. But in children’s practice is often positioned as an object and there is still the adverse treatment of children. The purpose of this research is to analyze legal protection against perpetrators of criminal acts in the judicial process in Indonesia. The method of approach used case studies, by analyzing 14 judges’ decisions in the courts of Banjarmasin and Martapura and conducting interviews with 4 judges who have dealt with the matter as well as the mediation facilitator. The results of legal protection research against child perpetrators of criminal acts in the judicial process in Indonesia has not been executed optimally. Judges are more severed by dropping jail sentence as much as 85.7% and 13.3% completed with versions by giving action reverted to his parents. A version effort as a form of child protection is still less successful because the judge considers the juridical aspect of the law, doubting the effectiveness of action sanctions, less feeling the criminological, sociological and psychological issues. In disregarding the matter, the child judges lack the information from the witness of the objective conditions of the defendant physically, psychic and social terms of the child, because the position of independent judge is not tied to the report of the supervisor until the judge Many more decided to provide a deterrent effect by providing coaching at the children’s Special Development Board to obtain service, care, education and training, better coaching until the time of the criminal completed.